Creation and implementation of the Ottawa Handbook of Emergency Medicine - Endres, Kaitlin; Anjum, Omar; Syed, Shahbaz (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Implication Statement: Medical students face multiple academic challenges during their transition to clerkship, including the ability to navigate various educational resources and translate acquired knowledge clinically. The Ottawa Handbook of Emergency Medicine (EM) was created by referencing EM textbooks and relevant literature, followed by a local peer-review process. A website metrics assessment was performed to assess student uptake. Implementation of the Ottawa Handbook of EM across Canadian clerkship curriculums is anticipated to bridge the EM knowledge gap for junior learners.